Perception of Special Needs Dentistry education and practice amongst Australian dental auxiliary students. (11th October 2017) - Borromeo, G. L.; Ahmad, M. S.; Buckley, S.; Bozanic, M.; Cao, A.; Al‐Dabbagh, M.; Athale, A.
Abstract: Introduction: The role of dental auxiliaries in collaborative care of patients with special needs is compelling. This study was undertaken to investigate the perceptions of Special Needs Dentistry (SND) education and practice amongst students enrolled in Australian programmes in dental auxiliary, namely dental hygiene, dental therapy and oral health therapy (DH/DT/OHT). Materials and methods: All Australian institutions offering DH/DT/OHT programmes (n = 14) were invited to participate in a self‐administered questionnaire survey, conducted online, involving students across all academic years. Twelve institutions agreed to participate, but only five institutions were included in the final analysis, with a student response rate of 31.1%. Answers to open‐ended questions were coded and grouped for measurement of frequencies. Quantitative data were analysed via chi‐squared and Fisher's exact tests (significance taken as P  < .05). Results: The majority of students could not define SND (87.0%) were not aware of the existence of this specialty (53.5%) and did not have clinical experience treating patients with special needs (68.9%). Nevertheless, they felt comfortable and positive about treating these patients independently. Most agreed that they should receive clinical and didactic education in SND, with many of them expressing interest in pursuing a specialty training in this field. Conclusion: DH/DT/OHT students' comfort levels, positive attitudes and supportiveness for SND suggested positive implications for these practitioners to partake in multidisciplinary management of patients with special needs, thus indicating the need for standardised training requirements and practice guidelines in this area of care.